Pengaruh Pendayagunaan Dana Zakat Produktif Terhadap Peningkatan Usaha Mikro Kecil dan Menengah Mustahik di Kota Surabaya - Muafif, Darul; Khoirul Anwar, Moch (Universitas Negeri Surabaya, 2022)
Zakat has enormous potential in encouraging the growth of the Indonesian economy either in short or long term. Analysis of the Zakat Potential Mapping Index by the BAZNAS Puskas found that in 2018 the potential for zakat in Indonesia had reached 233 trillion rupiah or 3% of Indonesia's GDP. From this figure, if zakat funds are allocated in the mustahiq economic empowerment program, it may certainly lead to sustainable benefits. The method used was quantitative with simple linear regression analysis. The results of this study indicated that the utilization of productive zakat funds had a positive effect on increasing mustahik's micro, small and medium enterprises in the city of Surabaya. These results also implied that the utilization of zakat was one of the things that affected the improvement of mustahik's micro, small and medium enterprises in the city of Surabaya